2020
DOI: 10.1101/2020.09.12.20193235
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of COVID-19 in diabetic kidney disease and chronic kidney disease: A population-based study

Abstract: Background: The spectrum of pre-existing renal disease is known as a risk factor for severe COVID-19 outcomes. However, little is known about the impact of COVID-19 on patients with diabetic nephropathy in comparison to patients with chronic kidney disease. Methods: We used the Mexican Open Registry of COVID-19 patients 11 to analyze anonymized records of those who had symptoms related to COVID-19 to analyze the rates of SARS-CoV-2 infection, development of COVID-19 pneumonia, admission, intubation, Intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 27 publications
3
32
0
Order By: Relevance
“…Several previous single studies and meta-analyses indicated that DM, CKD, hypertension and CVD might be risk factor and promoter of severity and mortality for SARS-COV-2 infection [26]. It is possible that mechanism mediated by ACE2 receptor links patients with these underlying diseases with a higher risk of SARS-COV-2 infection and death [31,46,47]. To date, some studies evaluated the proportion and mortality of SARS-COV-2 infection in the Iranian DM, CKD, hypertension and CVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous single studies and meta-analyses indicated that DM, CKD, hypertension and CVD might be risk factor and promoter of severity and mortality for SARS-COV-2 infection [26]. It is possible that mechanism mediated by ACE2 receptor links patients with these underlying diseases with a higher risk of SARS-COV-2 infection and death [31,46,47]. To date, some studies evaluated the proportion and mortality of SARS-COV-2 infection in the Iranian DM, CKD, hypertension and CVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to rank (with a cut off score 4), the enriched known or reported comorbid conditions or long-term complications are lupus erythematosus (Rank-1) [100], depressive disorder / mental depression (Rank-2) [30, 101], hepatitis C (Rank-3) [102], breast cancer (Rank-4) [75], arthritis (Rank-5) [103], asthma (Rank-6) [10, 77], liver cancer (Rank-6) [78], tuberculosis (Rank-7) [104, 105], diabetes (Rank-8) [82], myocardial infarction (Rank-9) [35, 106], macular degeneration (Rank-9) [80], chronic kidney disease (Rank-9) [56, 57], arteriosclerosis (Rank-10) [107], ulcerative colitis (Rank-10) [108], liver cirrhosis (Rank-11) [12, 109], sepsis / septicaemia /septic shock (Rank-11) [60, 81], other autoimmune diseases (Rank-12) [49, 50], cerebrovascular accident / stroke (Rank-13) [110], congenital anemia (Rank-13) [111], COPD (Rank-13) [86], multiple myeloma (Rank-14) [112], hypertensive disease (Rank-14) [9, 113], dyslipidemia (Rank-15) [93], metabolic syndrome X (Rank-15) [51, 114], osteoporosis (Rank-16) [91], prostate cancer (Rank-17) [115], psoriasis (Rank-17) [116], leukemia (Rank-18) [117, 118], long QT syndrome (Rank-18) [119], dementia (Rank-18) [120], schizophrenia (Rank-18) [121], intellectual disability (Rank-18) [122, 123], diabetic kidney disease/ diabetic nephropathy (Rank-18) [124]etc.…”
Section: Resultsmentioning
confidence: 99%
“…In individuals with and without diabetes, chronic kidney disease (CKD) is an independent risk factor for mortality in COVID-19 ( ERA-EDTA, 2021 ; Williamson et al, 2020 ). However, compared to non-diabetic individuals with CKD, individuals with diabetic nephropathy have a significantly greater probability of developing adverse outcomes in COVID-19 ( Leon-Abarca et al, 2020 ). Holman et al (2020) showed a negative linear relationship between eGFR and adverse COVID-19 outcomes in individuals with diabetes.…”
Section: Microvascular Complications Of Diabetes As a Risk Factor For Severe Covid-19mentioning
confidence: 99%